Decline in prevalence and risk of helicobacter pylori in kidney transplant recipients: A systematic review and meta‐analysis. Issue 3 (21st May 2017) - Cheungpasitporn, Wisit; Thongprayoon, Charat; Wijarnpreecha, Karn; Mitema, Donald G.; Mao, Michael A.; Nissaisorakarn, Pitchaphon; Podboy, Alexander; Kittanamongkolchai, Wonngarm; Sakhuja, Ankit; Erickson, Stephen B.
Abstract: Objective: The study's aims were (1) to investigate the prevalence and (2) to assess the risk of Helicobacter pylori (H. pylori) infection in kidney transplant recipients. Methods: A comprehensive literature search was performed from inception until September 2016. Studies that reported prevalence, relative risks, odd ratios, or hazard ratios of H. pylori among kidney transplant recipients were included. Pooled risk ratios and 95% CI were calculated using a random‐effect model. Results: Eleven observational studies with 2545 kidney transplant recipients were enrolled. Between year 1990 and 2000, the estimated prevalence of H. pylori among people with kidney transplant was 50% (95% CI: 31% to 68%), with a prevalence of 46% (95% CI: 23% to 70%) in high‐income countries and 55% (95% CI: 22% to 86%) in middle‐income countries, respectively. From year 2000 to 2016, the estimated prevalence of H. pylori among people with kidney transplant was 35% (95% CI: 26% to 45%), with a prevalence of 28% (95% CI: 19% to 37%) in high‐income countries and 45% (95% CI: 38% to 51%) in middle‐income countries. Data regarding prevalence of H. pylori infection in low‐income countries were limited. The pooled RR of H. pylori in kidney transplant recipients was 0.57 (95% CI: 0.33 to 1.00) when compared to people with non‐transplant. Conclusions: There has been a decline in prevalence of H. pylori in kidney transplant recipients with the overall estimated prevalence of H. pylori in kidney transplant recipients of 35%, particularly in both high‐income and middle‐income countries. Also, our meta‐analysis demonstrates a potential decreased risk of H. pylori infection in kidney transplant recipients compared with non‐transplant populations.